An NMR Method To Pinpoint Supramolecular Ligand Binding to Basic Residues on Proteins. Issue 46 (13th October 2017) - Hogeweg, Anna; Sowislok, Andrea; Schrader, Thomas; Beuck, Christine
Abstract: Targeting protein surfaces involved in protein–protein interactions by using supramolecular chemistry is a rapidly growing field. NMR spectroscopy is the method of choice to map ligand‐binding sites with single‐residue resolution by amide chemical shift perturbation and line broadening. However, large aromatic ligands affect NMR signals over a greater distance, and the binding site cannot be determined unambiguously by relying on backbone signals only. We herein employed Lys‐ and Arg‐specific H2(C)N NMR experiments to directly observe the side‐chain atoms in close contact with the ligand, for which the largest changes in the NMR signals are expected. The binding of Lys‐ and Arg‐specific supramolecular tweezers and a calixarene to two model proteins was studied. The H2(C)N spectra track the terminal CH2 groups of all Lys and Arg residues, revealing significant differences in their binding kinetics and chemical shift perturbation, and can be used to clearly pinpoint the order of ligand binding. Abstract : Lysine‐ and arginine‐specific NMR experiments were conducted to selectively observe the side‐chain atoms involved in the binding of supramolecular tweezers and to reveal the distinct binding order to multiple sites on a protein surface.